Effect of Loading Method and Mean Stress on Fatigue Strength of Super Duplex Stainless Steel - Udo, Ryujiro; Nishikawa, Hide-aki; Hato, Hisamitsu; Miyazaki, Katsumasa; Masaki, Kiyotaka; Numakura, Hiroshi (Tetsu-to-Hagane, 2017)
As a first step toward building a database of fatigue strength of super duplex stainless steel S32750, fatigue tests have been conducted by three methods, axial loading, plane bending and rotating bending, and with some different values of stress ratio R ranging from –1 to 0.4. The fatigue limits from the bending tests turned out appreciably higher than those from the axial loading. This is attributed to a lower stress amplitude than the nominal value designed in the bending tests, which results from partial yielding in the surface region. The influence of the partial yielding on the stress amplitude has been corrected for by calculating the non-linear stress distribution inside the specimen by following the method proposed by Koe et al. (1983). The corrected values of the fatigue strength from the bending tests match those from the axial loading. With this correction to both the mean stress and the stress amplitude, the effects of varying mean stress on the fatigue limit follows modified Goodman’s law, and the fatigue strengths at shorter times form a universal S-N diagram by employing the equivalent stress amplitude proposed by Smith, Watson and Topper (1970), except for a single set of data from a test with a high mean stress, R=0.4.